Indoor black carbon of outdoor origin and oxidative stress biomarkers in patients with chronic obstructive pulmonary disease - Grady, S. T.; Koutrakis, P.; Hart, J. E.; Coull, B. A.; Schwartz, J.; Laden, F.; J.J. Zhang; Gong, J.; Moy, M. L.; Garshick, E. (Environment International, 2018)
OBJECTIVES: We assessed relationships between indoor black carbon (BC) exposure and urinary oxidative stress biomarkers, 8-hydroxy-2'-deoxyguanosine (8-OHdG) and malondialdehyde (MDA), in participants with chronic obstructive pulmonary disease (COPD). METHODS: Eighty-two participants completed in-home air sampling for one week prior to providing urine samples up to four times in a year. Weekly indoor and daily outdoor concentrations were used to estimate indoor daily lags and moving averages. There were no reported in-home BC sources, thus indoor levels closely represented outdoor BC infiltration. Mixed effects regression models with a random intercept for each participant were used to assess relationships between indoor BC and 8-OHdG and MDA, adjusting for age, race, BMI, diabetes, heart disease, season, time of urine collection, urine creatinine, and outdoor humidity and temperature. RESULTS: There were positive effects of BC on 8-OHdG and MDA, with the greatest effect the day before urine collection (6.9% increase; 95% CI 0.9-13.3%, per interquartile range: 0.22mug/m(3)) for 8-OHdG and 1 to 4days before collection (8.3% increase; 95% CI 0.03-17.3% per IQR) for MDA. Results were similar in models adjusting for PM2.5 not associated with BC and NO2 (10.4% increase, 95% CI: 3.5-17.9 for 8-OHdG; 8.1% increase, 95% CI: -1.1-18.1 for MDA). Effects on 8-OHdG were greater in obese participants. CONCLUSIONS: We found positive associations between BC exposure and 8-OHdG and MDA, in which associations with 8-OHdG were stronger in obese participants. These results suggest that exposure to low levels of traffic-related pollution results in lipid peroxidation and oxidative DNA damage in individuals with COPD.
Keywords: copd; pollution; Urinary oxidative stress